Wage Premia for Education and Location, By Gender and Race in South Africa - T. Paul Schultz; Germano Mwabu (Yale University, Economic Growth Center, 1998)
Despite the lower quality of education provided Africans compared with whites in South Africa, the percentage wage gains associated with additional years of primary, secondary, and higher education are substantially larger for Africans than for whites in 1993, and they increase for both race groups at higher levels of education. The lower quantity (or political quotas) of education received by Africans than whites is a simple explanation for the wage structure documented in this paper. The other two racial groups, colored (mixed races) and Indians, occupy intermediate positions between whites and Africans in terms of both the quantity of education received and wage returns to those levels of education. As barriers to employment by race are dismantled in South Africa, wage differences between races are likely to diminish, while wage differences within race groups may well widen. Quantitative expansion of educational opportunities for nonwhites at the secondary and higher education levels seems to be overdue.
Keywords: J31; I21; H52; 330; Wage Structure; Educational Quotas; Returns to Education; South Africa; Lohnstruktur; Lohnstruktur; Bildungsertrag; Rasse; Südafrika